Chyle leak following neck dissection: lesson learned - Mohd Yasim, Mohd Nur Afiq; K, Noor Tilawatu; Mahno, Noor Ezmas (Faculty of Medicine, UKM, 2023)
Introduction: Chyle leak is a rare and serious complication that may occurs following head and neck surgery. Although the reported incidence is less that 2.5%, it may cause significant local and systemic problems such as poor wound healing, fistula formation, progression into chylothorax, secondary bacterial infection, hypovolemia and electrolytes disturbances. Case Report: We reported two cases of chyle leak following total thyroidectomy and neck dissection, both done for papillary thyroid carcinoma. First patient developed chyle leak and subsequent chylothorax, diagnosed during early postoperative period after we noted milky drainage from her left neck drain. Chest radiograph confirmed the diagnosis and she was treated conservatively with peripheral nutrition support, Medium-Chain Triglyceride oil as well as subcutaneous octreotide. Second patient however had a delayed presentation with neck collection noted during clinic follow up 2 weeks post-surgery. As such, in addition to the above measures employed for first patient, she required percutaneous drainage to drain the collection. Both patients successfully recovered well and does not require any additional surgery. Conclusion: Chyle leak and its sequalae of problems can be a challenging postoperative complication to deal with and prevention of the complication is therefore paramount. If such complication however still occur, prompt recognition of its occurrence and institution of correct management is vital in order to prevent further morbidity. This may be achieved by having high index of suspicion and sound understanding of the anatomy, physiology and pathophysiology of the condition.